SPECIFIC CHARACTERISTICS OF CHILDREN'S FEEDING IN CONGENITAL DEFORMITIES OF THE UPPER LIP AND PALATE (Conference Zone, 2022)
This article presents recommendations for feeding a child with congenital clefts of the upper lip and palate. These recommendations can be used by parents of children with rhinolalia, specialists in the referral process and in the organization of ablation with children of this category. Also, in the article, the uniqueness of the process of eating food, the specific characteristics of sucking, chewing and swallowing in children are revealed, and the methods of correctional speech therapy that allow indirect influence on the phases of swallowing are described.